(3GdbSWGS GdeSJbjes - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3GdaVd Hf CMeO Hf eMeO Hf eMeO GdHUQj s)
(3ChdgG (B:s
(3GdMeO ddg JYGdi ChdkG hCUdj Ydi QShdg GdeUWai KGfjkG hCbhd ENhGfi gd ajce ef jYjQfi SeYg abdJ CeG ejRGf GdQCj hGdbjGS aMGT ddg Cf CYJUe Hg s
(3BNQgG (B:s
(3hLYdhG GdJYdjeGJ GdfHhjI gHGA efKhQG acd Pdc ef aUhd GdLGgdjf hOYhGge ai fUQI GdOjf efUH GdYGQajf Ef QHc gh CYde HGdegJOjf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
Keywords: (3GdJUha hGdBOGH GdTQYjIs